2014
DOI: 10.2136/vzj2014.06.0064
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Leachate Water Quality Trends from a Broiler‐Litter‐Amended Udult in a Karst Region

Abstract: Application of broiler (Gallus gallus) litter (BL) to pasturelands in karst regions like the Ozark Highlands can potentially reduce water quality due to leaching of BL‐derived nutrients and trace metals. The objective of this study was to determine long‐term linear trends in drainage and soil leachate water quality under natural precipitation from a silt‐loam soil amended annually with BL at three application rates (0 [control], 5.6 [low], and 11.2 [high] Mg BL ha−1]. Automated equilibrium tension lysimeters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Similar results of high P concentrations in leachate above the levels responsible for eutrophication of water bodies were reported by McMullen, Brye, Daigh, et al. (2014) and Pirani et al. (2007) based on long‐term natural rainfall studies in plots equipped with equilibrium‐tension lysimeters installed at 0.9‐m depth in a silty loam soil overlying kart geology of Northwest Arkansas.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results of high P concentrations in leachate above the levels responsible for eutrophication of water bodies were reported by McMullen, Brye, Daigh, et al. (2014) and Pirani et al. (2007) based on long‐term natural rainfall studies in plots equipped with equilibrium‐tension lysimeters installed at 0.9‐m depth in a silty loam soil overlying kart geology of Northwest Arkansas.…”
Section: Resultssupporting
confidence: 86%
“…Even if leachate P losses do not affect surface or groundwater quality short‐term, results indicate that karst‐derived soils are susceptible to deep soil profile leaching, which may increase P concentration of deeper soil layers and may serve as a source of P once remobilized (Sharpley et al., 2013). Further, the effects of elevated nutrient and trace metal concentration associated with litter application can affect surface and subsurface water quality long‐term even after the cessation of poultry litter application (McMullen, Brye, Daigh, et al., 2014; McMullen, Brye, Miller, et al., 2014; Menjoulet et al., 2009; Pirani et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal leachate pH was slightly more acidic with time and averaged 6.2 across BL rates (Table 2). As would be expected from their rather large BL concentrations (McMullen et al, 2014b), seasonal FWM leachate Ca, K, Na, and Mg concentrations were numerically greatest among all other plant nutrients and trace metals measured in the study and averaged 15.3, 16.0, 12.0, and 5.3 mg L −1 , respectively, across BL rates with time (Table 2). The C concentration of applied BL was largest among all elements measured; however, seasonal FWM leachate DOC concentrations averaged only 3.0 mg L −1 across BL rates with time (Table 2).…”
Section: Flow-weighted Mean Concentrationssupporting
confidence: 57%
“…After 8 yr of continuous measurements associated with the original field study, McMullen et al (2014b) reported 8‐yr trends (May 2003–May 2011) in drainage and leachate water quality, summarized as annual cumulative drainage and annual FWM concentrations and loads of soluble trace metals and plant nutrients. Their results showed that average annual drainage and leachate pH, electrical conductivity (EC), and FWM concentrations and loads of NO 3 –N, PO 4 –P, Cd, Cr, K, total P, Zn, and dissolved organic C (DOC) did not vary with time and were unaffected by the BL application rate (McMullen et al, 2014b). However, average annual FWM concentrations and loads of NH 4 –N, As, Mn, and Ni decreased while Cu and Se increased during the continuous 8‐yr period but were also unaffected by BL rate (McMullen et al, 2014b).…”
mentioning
confidence: 99%
“…In 2011, typical roxarsone levels in commercial poultry feed were 30–50 mg/kg [ 17 ]. Elevated As levels in runoff water and soil pore water from fields treated with poultry litter are well documented [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Roxarsone is more strongly absorbed in some soils than in others [ 25 ].…”
Section: Introductionmentioning
confidence: 99%